Pharmacists’ Knowledge and Attitudes Regarding Biologics and Biosimilars: A Literature Review - Trajculeski, Marija; Naumovska, Zorica; Gjorgieva Ackova, Darinka; Darkovska Serafimovska, Marija; Lazarova, Biljana; Smilkov, Katarina (Archives of Pharmacy, 2026)
Advancements in biologic therapies have become crucial for managing both acute and chronic illnesses. In addition, the growing presence of biosimilar medications presents significant opportunities for reducing healthcare costs and expanding patient access to essential biologic treatments. Pharmacists, as part of the healthcare system, play an important role in the use of this group of medications. The purpose of this literature review is to examine existing research on pharmacists’ knowledge and attitudes toward originator biologics and biosimilars, as well as assessing the need for further educational initiatives in this area. A digital search of literature was carried out through journal databases, such as PubMed, and Scopus, using selected search terms, and applying the inclusion criteria that match the aim of the research. The majority of studies that are subject to evaluation have been conducted, in the form of short surveys, revealing that most of the pharmacists are familiar with the biologic and biosimilar medicines, however their measured knowledge was less extensive than their self-assessed knowledge. Pharmacists’ knowledge and attitudes towards biologics exhibit a wide variation. Insufficient clinical experience and need for additional education were identified as prerequisites for greater inclusion of biologic originator and biosimilar medicines in clinical practice.